Pengaruh Supportive Leardership Terhadap Job Performance dengan Job Satisfaction Sebagai Variabel Intervening Pada Karyawan Hotel X Sidoarjo - Miko Arko (Jurnal Bisnis dan Keuangan, 2020)
The purpose of this study is to prove the influence of supportive leadership and performance through job satisfaction as a mediator. The method used in this study is quantitative with data collection techniques through the distribution of questionnaires in the study sample, as many as 74 employees of Hotel X Sidoarjo. The data analysis technique used is SPSS and Sobel test to determine the mediating effect. This study found that: (1) leadership supported positive and significant effect on job satisfaction with a beta coefficient of 0,618 (0.000 <0.05); (2) job satisfaction has a positive and significant effect on performance with a beta coefficient of 0,348 (0.000 <0.05); and (3) job satisfaction succeeded in mediating the effect of support on work performance with the sobel test results of 2.730 (0.006 <0.05).